Large-scale STI services in Avahan improve utilization and treatment seeking behaviour amongst high-risk groups in India: an analysis of clinical records from six states - Gurung Anup; Narayanan Prakash; Prabhakar Parimi; Das Anjana; Ranebennur Virupax; Tucker Saroj; Narayana Laxmi; R Radha; Prakash K; Touthang J; Sono Collins Z; Wi Teodora; et al. (BMC, 2011)
Abstract Background Avahan, the India AIDS Initiative, implemented a large HIV prevention programme across six high HIV prevalence states amongst high risk groups consisting of female sex workers, high risk men who have sex with men, transgenders and injecting drug users in India. Utilization of the clinical services, health seeking behaviour and trends in syndromic diagnosis of sexually transmitted infections amongst these populations were measured using the individual tracking data. Methods The Avahan clinical monitoring system included individual tracking data pertaining to clinical services amongst high risk groups. All clinic visits were recorded in the routine clinical monitoring system using unique identification numbers at the NGO-level. Visits by individual clinic attendees were tracked from January 2005 to December 2009. An analysis examining the limited variables over time, stratified by risk group, was performed. Results A total of 431,434 individuals including 331,533 female sex workers, 10,280 injecting drug users, 82,293 men who have sex with men, and 7,328 transgenders visited the clinics with a total of 2,700,192 visits. Individuals made an average of 6.2 visits to the clinics during the study period. The number of visits per person increased annually from 1.2 in 2005 to 8.3 in 2009. The proportion of attendees visiting clinics more than four times a year increased from 4% in 2005 to 26% in 2009 (p<0.001). The proportion of STI syndromes diagnosed amongst female sex workers decreased from 39% in 2005 to 11% in 2009 (p<0.001) while the proportion of STI syndromes diagnosed amongst high risk men who have sex with men decreased from 12% to 3 % (p<0.001). The proportion of attendees seeking regular STI check-ups increased from 12% to 48% (p<0.001). The proportion of high risk groups accessing clinics within two days of onset of STI-related symptoms and acceptability of speculum and proctoscope examination increased significantly during the programme implementation period. Conclusions The programme demonstrated that acceptable and accessible services with marginalised and often difficult-to-reach populations can be brought to a very large scale using standardized approaches. Utilization of these services can dramatically improve health seeking behaviour and reduce STI prevalence.